2D phase behaviors of colloidal ellipsoids and rods - Wang, Huaguang; Zhang, Zexin; Ling, Xinsheng Sean (Frontiers in Physics, 2022)
In recent years, the shape of particles has emerged as a key factor influencing their self-assembly and phase behaviors. Understanding the phase behaviors of systems containing shape anisotropic particles remains challenging. In this mini-review, we will summarize our recent experimental studies on the phase behaviors of colloidal systems in which all or part of particles have anisotropic shapes. We focus on two types of shape anisotropic particles, ellipsoids and rods. In particular, it was found that (i) in equilibrium, the anisotropic particles form a nematic phase in 2D, (ii) when quenched, they can form a stable glassy state with a two-step glass transition, and (iii) when they are dispersed as impurities in a 2D colloidal crystal of spheres, they can destroy the 2D crystal phase. We will discuss the current challenges in the field.